The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1016/j.bbalip.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sterol dynamics

Abstract: We review the cellular mechanisms implicated in cholesterol trafficking and distribution. Recent studies have provided new information about the distribution of sterols within cells, including analysis of its transbilayer distribution. The cholesterol interaction with other lipids and its engagement in various trafficking processes will determine its proper level in a specific membrane; making the cholesterol distribution uneven among the various intracellular organelles. The cholesterol content is important s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
253
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(262 citation statements)
references
References 157 publications
(179 reference statements)
8
253
0
1
Order By: Relevance
“…It is possible that to facilitate cholesterol egress from LE/LY, NPC2 has to interact with NPC1 to deliver cholesterol to the limiting membrane for egress (19,27), whereas a CD can bypass that requirement and deliver cholesterol directly to the limiting membrane. Once in the limiting membrane, cholesterol could leave the LE/LY by vesicular or nonvesicular transport processes (29) to be delivered to other organelles.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that to facilitate cholesterol egress from LE/LY, NPC2 has to interact with NPC1 to deliver cholesterol to the limiting membrane for egress (19,27), whereas a CD can bypass that requirement and deliver cholesterol directly to the limiting membrane. Once in the limiting membrane, cholesterol could leave the LE/LY by vesicular or nonvesicular transport processes (29) to be delivered to other organelles.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its fast flip-flop rate, the cholesterol distribution across the two leaflets of the plasma membrane has been quite challenging to determine, with experiments suggesting either an outer or inner leaflet enrichment (23,63). A recent study, based on a large scale molecular dynamics simulation, showed an asymPlasma Membrane Cholesterol in Steroidogenesis DECEMBER 9, 2016 • VOLUME 291 • NUMBER 50 metrical distribution of cholesterol, in which the outer leaflet of the plasma membrane included 54% of the total cholesterol with a slightly higher cholesterol content than the inner leaflet (comprising 46%) (62).…”
Section: Discussionmentioning
confidence: 99%
“…A series of metabolic labeling studies of Leydig and adrenal cell lines with radiolabeled acetate and cholesterol led them to suggest the importance of the plasma membrane. Among the cell membranes, the plasma membrane has the highest concentrations of cholesterol, with the next highest concentrations observed in endosomal recycling compartments and the Golgi apparatus (23). It is surprising that mitochondria, the site where steroid synthesis is initiated, and the endoplasmic reticulum (ER), where cholesterol is synthesized de novo, have lower concentrations of cholesterol than other cell membranes (23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonvesicular lipid transport between membranes could be mediated by spontaneous lipid transport, in which a lipid monomer is diffused through the cytosol from a donor to the acceptor membrane. Given that most cellular lipids are highly hydrophobic, their diffusion through an aqueous phase is very slow and insufficient to support substantial transport of most lipids (Jones and Thompson 1989;Mesmin and Maxfield 2009). Nevertheless, spontaneous lipid transport can be greatly facilitated at membrane contact sites (MCSs) (Levine 2004;Holthuis and Levine 2005) and/or by lipid-transfer proteins (LTPs) (Lev 2010).…”
mentioning
confidence: 99%